Genome Size Diversity in Lilium (Liliaceae) Is Correlated with Karyotype and Environmental Traits - Du, Yun-peng; Bi, Yu; Zhang, Ming-fang; Yang, Feng-ping; Jia, Gui-xia; Zhang, Xiu-hai (Frontiers in Plant Science, 2017)
Genome size (GS) diversity is of fundamental biological importance. The occurrence of giant genomes in angiosperms is restricted to just a few lineages in the analyzed genome size of plant species so far. It is still an open question whether GS diversity is shaped by neutral or natural selection. The genus Lilium, with giant genomes, is phylogenetically and horticulturally important and is distributed throughout the northern hemisphere. GS diversity in Lilium and the underlying evolutionary mechanisms are poorly understood. We performed a comprehensive study involving phylogenetically independent analysis on 71 species to explore the diversity and evolution of GS and its correlation with karyological and environmental traits within Lilium (including Nomocharis). The strong phylogenetic signal detected for GS in the genus provides evidence consistent with that the repetitive DNA may be the primary contributors to the GS diversity, while the significant positive relationships detected between GS and the haploid chromosome length (HCL) provide insights into patterns of genome evolution. The relationships between GS and karyotypes indicate that ancestral karyotypes of Lilium are likely to have exhibited small genomes, low diversity in centromeric index (CVCI) values and relatively high relative variation in chromosome length (CVCL) values. Significant relationships identified between GS and annual temperature and between GS and annual precipitation suggest that adaptation to habitat strongly influences GS diversity. We conclude that GS in Lilium is shaped by both neutral (genetic drift) and adaptive evolution. These findings will have important consequences for understanding the evolution of giant plant genomes, and exploring the role of repetitive DNA fraction and chromosome changes in a plant group with large genomes and conservation of chromosome number.